SISTEMAS FOTOVOLTAICOS INTEGRADOS À ARQUITETURA (BIPV): MOMENTO PRESENTE E POTENCIAL - Silveira, Flávia; Dias, Sofia; Schmid, Aloisio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The recent crossing of the cost barrier of US$ 1.0/W for photovoltaic (PV) panels allows new prospects for a massive use of renewable energies. Now, there is the imperative to identify and organize a large area of collecting surfaces, particularly in the urban realm. This paper presents a review of photovoltaic energy and some aspects of building integrated photovoltaic (BIPV) in order to approach the theme and know the Brazilian context of solar energy.